Anterolateral ligament reconstruction with autologous grafting: A biomechanical study. (May 2017) - Monaco, E.; Lanzetti, R.M.; Fabbri, M.; Redler, A.; De Carli, A.; Ferretti, A.
Abstract: Background: To evaluate the reliability of the Iliotibial band compared to gracilis tendon as a graft to be used in anterolateral ligament reconstruction. Methods: Gracilis tendon and a strip of Iliotibial band compared were harvested from 8 fresh human cadaveric knees. The gracilis tendon was prepared to obtain a graft of 10 cm in length (Group 1). Iliotibial band compared was prepared to obtain a graft of 10 cm in length and 0.5 cm in width from the middle portion (Group 2). All the specimens were fixed on a servo hydraulic tensile machine with dedicated cryo-clamp. The loading protocol, used to compare the previously published results of ultimate failure load and Stiffness of the anterolateral ligament (Group 3), included a cyclic preconditioning between 10 and 25 N at 0.1 Hz for 10 cycles and then a load to failure test at 20 mm/min. Findings: Gracilis tendon showed higher Ultimante Failure Load and stiffness when compared to a strip of Iliotibial band. Gracilis tendon and a strip of Iliotibial band compared showed higher Ultimante Failure Load and stiffness when compared with native anterolateral ligament as reported by Kennedy. Interpretation: Both grafts tested in the present studies are suitable for an anatomical anterolateral ligament reconstruction. Highlights: Gracilis and Iliotibial-band are the most used graft for the ALL reconstruction. Gracilis and Iliotibial-band showed higher UFl than native ALL. Gracilis and Iliotibial-band showed higher stiffness than native ALL. Gracilis and Iliotibial-band are suitable graft for ALL reconstruction.